Dental Students' Interpretations of Digital Panoramic Radiographs on Completely Edentate Patients. Issue 3 (1st March 2018) - Kratz, Richard J.; Nguyen, Caroline T.; Walton, Joanne N.; MacDonald, David
Abstract : The ability of dental students to interpret digital panoramic radiographs (PANs) of edentulous patients has not been documented. The aim of this retrospective study was to compare the ability of second‐year (D2) dental students with that of third‐ and fourth‐year (D3‐D4) dental students to interpret and identify positional errors in digital PANs obtained from patients with complete edentulism. A total of 169 digital PANs from edentulous patients were assessed by D2 (n=84) and D3‐D4 (n=85) dental students at one Canadian dental school. The correctness of the students' interpretations was determined by comparison to a gold standard established by assessments of the same PANs by two experts (a graduate student in prosthodontics and an oral and maxillofacial radiologist). Data collected were from September 1, 2006, when digital radiography was implemented at the university, to December 31, 2012. Nearly all (95%) of the PANs were acceptable diagnostically despite a high proportion (92%) of positional errors detected. A total of 301 positional errors were identified in the sample. The D2 students identified significantly more (p=0.002) positional errors than the D3‐D4 students. There was no significant difference (p=0.059) in the distribution of radiographic interpretation errors between the two student groups when compared to the gold standard. Overall, the category of extragnathic findings had the highest number of false negatives (43) reported. In this study, dental students interpreted digital PANs of edentulous patients satisfactorily, but they were more adept at identifying radiographic findings compared to positional errors. Students should be reminded to examine the entire radiograph thoroughly to ensure extragnathic findings are not missed and to recognize and report patient positional errors.